2018
DOI: 10.1038/s41598-018-23620-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Eosinophils and Mast Cells in Functional Dyspepsia: an Ultrastructural Evaluation

Abstract: We recently identified mucosal mast cell and eosinophil hyperplasia in association with a duodenal impaired barrier function in functional dyspepsia (FD). We aimed to further describe the implication of these immune cells by assessing their activation state at the ultrastructural level and by evaluating the association between impaired epithelial integrity and immune activation. Duodenal biopsies were obtained from 24 FD patients and 37 healthy controls. The ultrastructure of mast cells and eosinophils was ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 28 publications
(46 reference statements)
3
45
2
3
Order By: Relevance
“…However, the staining of claudin‐1 was not on the apical side of duodenal epithelia in this study. A recent report by Vanheel presented no association between epithelial integrity and the number of mucosal eosinophils and mast cells . The present study found increased claudin‐3 mRNA expression in patients with FD.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the staining of claudin‐1 was not on the apical side of duodenal epithelia in this study. A recent report by Vanheel presented no association between epithelial integrity and the number of mucosal eosinophils and mast cells . The present study found increased claudin‐3 mRNA expression in patients with FD.…”
Section: Discussioncontrasting
confidence: 59%
“…Of the 10 studies that evaluated mast cell counts, 5 studies reported increased mast cell infiltration in the duodenum and 1 in the duodenal bulb. The pooled results showed increased duodenal mast cell counts (SMD = 0.66, 95%CI 0.20‐1.13, P = .005) in individuals with FD . There was heterogeneity observed among the studies ( I 2 = 82%, P < .001) but no publication bias was detected (Egger's test P = .833).…”
Section: Resultsmentioning
confidence: 88%
“…Nineteen studies examined eosinophil infiltration in FD. A pooled evaluation showed increased duodenal eosinophils in individuals with FD (SMD = 0.95, 95%CI 0.66‐1.24, P < .001) compared to controls (Figure A) . Although significant heterogeneity ( I 2 = 88%, P < .001) and publication bias (Egger's test P = .004, Figure B) were observed, no single publication was found to bias the results in the sensitivity analysis (Figure C).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations